ANALISIS DAMPAK PENETEPAN UU NO.28/2009 TERHADAP ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY (STUDI KASUS PADA PERUSAHAAN ROKOK DI BEI) - Nurfauziah Nurfauziah; Rossy Afiano (Optimum: Jurnal Ekonomi dan Pembangunan, 2013)
This study aims to analyze the differences in the average abnormal return and the average trading volume activity on tobacco companies on the Stock Exchange before and after the promulgation of Law No.28/2009 events. This study uses event study, which carried out observations of the average abnormal return and the average trading volume activity for 5 days before and 5 days after the event. Results of this study indicate there are differences in the average abnormal return and the average trading volume but no significant activity before and after the promulgation of Law No.28/2009 events, suggesting that market participants had anticipated with no rush to transactions, average abnormal return obtained is negative which means that the information content of the event is bad information. The average trading volume greater activity in the period before the event was announced this suggests that investors anticipate likely done in the period before the event announced.